Transmission risk behaviour at enrolment in participants in the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial. - Rodger, Aj; Lampe, Fc; Grulich, Ae; Fisher, M; Friedland, G; Phanuphak, N; Bogner, Jr; Pereira, Lc; Rietmeijer, C; Burman, W; Phillips, An (HIV medicine, 2015)
A proportion of HIV-positive people have condomless sex. Antiretroviral treatment (ART) reduces infectiousness, but a substantial proportion of HIV-diagnosed people are not yet on ART. We describe baseline self-reported risk behaviours in ART-naïve Strategic Timing of AntiRetroviral Treatment (START) trial participants.